Тайна золотой лихорадки: [повесть] / Фиона Келли - Келли Фиона (Черный котенок, 2005)
Экземпляры: ф.23 (2007) / Инвентарный номер: 50575 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: К 34 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)-44